Subcutaneous spirocercosis in a dog from Costa Rica and first molecular confirmation of Spirocerca lupi in Central America - Porras-Silesky, Catalina (2022)
Spirocerca lupi is the etiological agent of spirocercosis in canids from tropics and subtropics in the world. This parasite can lead to life threatening complications, including the formation of fibro and osteosarcomas. A 5-year- old crossbreed Maltese dog from Costa Rica was presented to a veterinary clinic with two nodules in the sub- cutaneous tissues of the cervical region. One of the nodules resolved with intramuscular antibiotic and anti- inflammatory treatment. However, the other nodule persisted and became purulent. The content of the nodule was excised releasing two coiled 3-cm reddish worms. Identity of the specimens was confirmed by amplifying an 850 bp fragment of the 18S rDNA. The obtained sequence showed 99.96% similarities with S. lupi from Hungary. The present study highlights the need of veterinary clinicians' awareness towards nematode aberrant migrations, and the require of molecular studies to gain insight into the parasite's evolutionary history.